Risk for imbalanced blood pressure pattern among incarcerated women: Middle-Range Theory - Gabrielle Pessôa da Silva; Camila Takáo Lopes; Marcos Venícios de Oliveira Lopes; Ryanne Carolynne Marques Gomes Mendes; Jaqueline Galdino Albuquerque Perrelli; Lívia Maia Pascoal; Suzana de Oliveira Mangueira; Francisca Márcia Pereira Linhares (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to develop a Middle-Range Theory for the Risk for imbalanced blood pressure pattern among incarcerated women. Methods: theoretical development study to obtain the theoretical-causal validity of the Nursing Diagnosis Risk for unstable blood pressure. The Middle-Range Theory was developed according to six stages: establishment of the approach to developing the theory; definition of the conceptual models to be later analyzed; definition of the main conceptions; a pictorial diagram; propositions; causal relationships and evidence for practice. Results: two attributes and 20 antecedents related to imbalanced blood pressure were identified, a pictorial diagram was developed, and nine theoretical propositions were presented. Conclusions: the theory developed here favors the diagnostic reasoning of nurses and contributes to planning actions to promote the cardiovascular health of incarcerated women. A new proposition for the diagnosis of Risk for unstable blood pressure was also structured with a new title, definition, and etiological factors.